Territorio y representación. Cartografía del obispado de Michoacán, 1716-1812 - Navarro López, América Alejandra (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
At the moment the study and analysis of the cartography for the investigations of historical type are an aspect little explored in our country. This, although the man acts in a defined point of the terrestrial surface and in a certain moment of his history; nevertheless, traditionally it has been considered to the history like the study of the human activity in his temporary dimension, as well as the geography is it in its space dimension. We coincide with Whitllesey when it assures that "all geography is historical." 1 could even be said that there is not geography without history, as well as neither there is history without geography. 2 in the historical investigation the space dimension should be then as important as the temporary dimension. The historical-cartographic analysis you can approach taking to the cartography like a technique combination and art, also like an expression of the geographical knowledge and of the interests that individuals and social groups had in the territory. Without stopping to admit that these last two factors are very important, in this work we have decided to make, for the Bishopric of Michoacán, a historical-cartographic study starting from figuring out the objective for which each map was made, at the same time that we analyze the evolution of the technique in the elaboration of the maps.

Actualmente el estudio y análisis de la cartografía para las investigaciones de tipo histórico es un aspecto poco explorado en nuestro país. Esto, a pesar de que el hombre actúa en un punto delimitado de la superficie terrestre y en un momento determinado de su historia; no obstante, tradicionalmente se ha considerado a la historia como el estudio de la actividad humana en su dimensión temporal, así como la geografía lo es en su dimensión espacial. Coincidimos con Whitllesey cuando asegura que "toda geografía es histórica". 1 Podría incluso decirse que no hay geografía sin historia, así como tampoco hay historia sin geografía. 2 En la investigación histórica la dimensión espacial debe ser entonces tan importante como la dimensión temporal. El análisis histórico-cartográfico se puede abordar tomando a la cartografía como una combinación de técnica y arte, también como una expresión de los conocimientos geográficos y de los intereses que individuos y grupos sociales tenían en el territorio. Sin dejar de admitir que estos dos últimos factores son muy importantes, en este trabajo hemos decidido hacer, para el Obispado de Michoacán, un estudio histórico-cartográfico a partir de desentrañar el objetivo para el cual fue hecho cada mapa, a la vez que analizamos la evolución de la técnica en la elaboración de los mapas.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2006-0003; Opción en historia de México; Cartografía; Obispado; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2354